Pancasila sebagai Landasan Ideologis bagi Pengembangan Keilmuan pada Komunitas Akdemik di Indonesia dan Tantangan Globalisasi - Jurgen R. Litualy; Andreas M D. Ratuanak (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
The flow of globalization and digitalization is a phenomenon that is present in our daily lives, both in material form and in our minds. In this digital era, people meet and interact in a globalized, seamless space and send ideas, opinions, behaviours, habits, cultures, and ideologies to each other. The impact of global social change that has also hit Indonesia with the rapid development of this technology, not only has the potential to have a positive effect on national life and humanity universally but can also have a negative impact. This is a literature study with a reflective and critical studies approach, which is presented in a descriptive-analytical critical manner as a doctrinal reflection and to formulate theoretical conclusions regarding Pancasila as an ideological foundation for the development of science in the academic community in Indonesia and the challenges of globalization that threaten it. This study found that in responding to this current situation, the resilience of the values ​​that are the basis for the development of science is greatly needed. In the current context, the values ​​of Pancasila can become a collective consciousness to maintain the preservation of national identity in the academic community and the results of its scientific development.